Monthly Variation of Physico-Chemical Parameters of Haleji lake, Sindh, Pakistan: Monthly Variation of Physico-Chemical Parameters of Haleji lake, Sindh, Pakistan - Rao, Shahina; Azmi, Muhammad Arshad (International Journal of Economic and Environmental Geology, 2019)
Present work is based on the physico-chemical parameters of Haleji lake. Physical factors and chemistry of lake water were analyzed with regular intervals. The color of water showed variation from light green to yellowish green, air temperature ranged between 20 °C to 35 °C, water temperature between 17 °C to 33 °C , pH 5.5 to 7.5, dissolved oxygen 2.04 mg/L to 6.44 mg/L, salinity 0.32 mg/L to 1.1 mg/L, alkalinity from 30 mg/L to 100 mg/L, acidity 10 to 96 mg/L, sulphate 4.5 mg/L to 305 mg/L, phosphate from 1 mg/L to 190 mg/L, and nitrates 9 mg/L to 270 mg/L during 2006, 2007 and 2008 respectively.